TMS320C54X-based coconut age classification system using the Hidden Markov Model - David, Raquel B. (1999)
For so many years now, the traditional tap system is still the method being used by coconut vendors to tell what meat type a coconut has. If a customer asks for a specific coconut type, they simply tap the coconut with their bolo, then based on the sound produced, will decide whether it is mala-kanin, mala-uhog, or mala-tainga. A coconut age classifier will be able to tell the age and type of a coconut based on the sound that will be produced upon tapping it. This will be useful in wholesale coconut industries wherein a lot of customers, particularly foreign traders, demand a particular type of meat depending on their applications. The researchers will create a model that will mimic the human ear and using this model, an unknown coconut sample can be classified as a mala-kanin, mala-tainga, or a mala-uhog.